Spanning three decades: global research wave and future prospects of broader autism phenotype—a visual researches by CiteSpace and VOS viewer - Qiao, Fu-Qiang; Li, Si-Ning; Du, Tong-Tong; Cheng, Wen-Ming; Sun, Ying-Ying; Qiang, Xu; Dong, Ya-Jie; Wang, Lei (Frontiers in Psychology, 2024)
Objectives To conduct a comprehensive review of the literature pertaining to the broader autism phenotype, the paper endeavors to delineate the key research directions and topics, document the current research trends, and furnish insightful analyses and novel perspectives to foster future advancements in the field, with the aid of CiteSpace and VOS viewer. Methods CiteSpace and VOS viewer are two kinds of software for visualizing citations that is intended to examine academic literature and identify possible sources of knowledge. The Web of Science Core Collection database was used to retrieve articles from 1994 to 2024 that discussed the autism phenotype in general. Following data collection, analyses were conducted using CiteSpace V.6.2.R4 (64-bit) on a number of topics, such as annual publication output, highly cited journals, affiliations with countries and institutions, eminent authors, cited references, and keywords. Knowledge maps, collaborative network analysis, cluster analysis, and strongest citation burst analysis were among the tools used to visualize the data. Results A total of 1,075 articles about the broader autism phenotype were found. Roughly speaking, the annual number of publications is rising. With 546 articles on the subject, the United States is the nation with the greatest amount of authority and influence (centrality of 0.32), with England (218 articles) and Canada (115 articles) coming in second and third, respectively. The cited journals and institutions are mainly from the United States. The research consistently emphasizes the academic achievement and engagement of broader autism phenotype when analyzing the most cited references and authors. Conclusion This study used CiteSpace to analyze the state of the larger autism phenotype field and then identified research frontiers and hotspots. As new findings are made, global trends in more thorough studies of the autism phenotype suggest that interest in these studies will only grow.